NIR‐II Fluorescent Protein Created by In Situ Albumin‐Tagging for Sensitive and Specific Imaging of Blood‐Brain Barrier Disruption - Jiajun Xu; Yijing Du; Ningning Zhu; Jia Li; Yuewei Zhang; Ding Zhou; Shoujun Zhu (Advanced Science)
Abstract Imaging albumin in vivo is a reliable strategy to visualize blood‐brain barrier (BBB) disruption by detecting the dye‐labeled albumin leaking into brain parenchyma. Although Evans Blue (EB) and indocyanine green (ICG) dyes have been applied to assess BBB impairment, their naked‐eye observation or near‐infrared‐I (NIR‐I) imaging window limit the imaging sensitivity and contrast for this promising “albumin‐based” strategy. Herein, an albumin‐specific tagged near‐infrared‐II (NIR‐II) probe is engineered as a chromophore to construct fluorescent proteins (FPs) in situ for assessing BBB disruption in stroke. The optimized chromophore, C7‐1080, can covalently bind to albumin through nucleophilic substitution, forming FPs without adjuvant. Notably, the albumin effectively acts as a brightness enhancer and stability regulator for chromophores through the tight clamping effect. Theoretical simulation, proteomics, and protein mutation techniques are employed to investigate the binding behavior between albumin and chromophore. The in situ NIR‐II FPs construction strategy facilitates high‐precision dual‐channel imaging of BBB disruption and cerebral vessels during ischemic stroke when combined with the IR‐808Ac probe. Overall, the in situ albumin‐specific tag holds promise for diagnosing and monitoring strokes, presenting a tool for investigating the progression and therapeutic responses of related diseases.